Incongruity, Humor, and Mark: Performance and the Use of Laughter in the Second Gospel (Mark 8.14–21) - Iverson, Kelly R. ca. 20./21. Jh. (2013)
Relatively little scholarly work has attempted to change the perception that the Bible is a non-humorous book. Drawing upon contemporary humor theory, this article explores how Mark's third sea crossing (8.14–21) is intended to evoke a humorous response. Although laughter emerges from the comedic depiction of the Twelve, humor complements the evangelist's broader theological agenda. In Mark, humor is a natural byproduct of performance and is a powerful means of communicating a central theme of the Gospel.
Keywords: Performance; Orality; Humor; Laughter; Disciples; Mark 8.14–21